Do I talk right? Teacher Talk in Teaching English - Mimma Anggrista; Syamsul Bahri Ys (Research in English and Education Journal, 2017)
This study investigated how the teachers used teacher talks in their classroom. This research was focused on analyzing how teachers in Pulo Aceh, Aceh Besar, used the features of teacher talk in improving students’ English speaking ability. SETT (Self Evaluation by Teacher Talk) designed by Walsh used to identify the features of teacher talk occurred in teaching and learning process. In addition, observation sheet was also used as the instrument of this study. From the findings, the writer found that there are eight of fourteen features used by the teachers in their classroom namely display question, extended teacher turn, teacher interruption, extended learner turn, extended wait-time, content feedback, form-focused feedback and direct repair. From these eight features, there were two of eight features used inappropriately by one of two teachers. Therefore, it can be concluded that the teachers has used teacher talk in their teaching and learning process, however the implementation of the features were not optimal. It is suggested the teacher should utilize more features of teacher talk in improving students’ ability in speaking so that the outcomes of the students in speaking is increased.